Methimazole-Induced Leukocytoclastic Vasculitis: A Case Report - Weeratian Tawanwongsri; Pamela Chayavichitsilp (Karger Publishers, 2019)
Major identifiable causes of leukocytoclastic vasculitis include certain infections and medications. Amongst antithyroid drugs, methimazole (MMI) is rarely implicated as a culprit drug. We report the first case, in Thailand, of MMI-induced leukocytoclastic vasculitis in a 41-year-old Thai female who had received MMI for relapsed Graves' disease. MMI was discontinued and cholestyramine at a dose of 4 g four times daily was given instead. Her rashes on both legs resolved dramatically at 1-week follow-up. However, thyroid function test revealed unimproved thyrotoxicosis. She subsequently underwent radioiodine ablation as a definitive treatment. There were neither recurrent skin lesions nor other systemic involvements during the 3-month follow-up period. Notably, the most crucial step in the management of drug-induced leukocytoclastic vasculitis is the discontinuation of the offending drug in order to avoid further progression of the disease. The administration of immunosuppressive agents may not be necessary in patients with mild severity and non-vital organ involvement.